2016
DOI: 10.1080/21695717.2016.1237414
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear microphonics recording during ABR threshold testing in children

Abstract: Objective: It is agreed that the cochlear microphonic (CM) arises mainly from the normal outer hair cells (OHCs) in cochlea. The aim of this research is to study the CM characteristics in different hearing profiles and reflect the usefulness of recording CM simultaneously during Auditory Brainstem Response (ABR) threshold testing in children. Methods: This is a retrospective study that included 33 cases comprised of children with autism spectral disorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 21 publications
1
6
0
3
Order By: Relevance
“…Previous studies showed that the amplitude of CM in AN patients with DPOAE absent was significantly lower than that in normal subjects and AN patients with DPOAE present, and the nonlinear characteristics decreased on the I/O function curve in patients without DPOAE response, with a more linear tendency in amplitude increasing. 15 , 18 , 19 , 20 In this study, under various stimulation intensities, the CM amplitude of OAE absent group was lower than that of OAE present group, consisted with previous studies. It also found that compared with OAE present group, the CM threshold was higher and duration was shorter in OAE absent group.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Previous studies showed that the amplitude of CM in AN patients with DPOAE absent was significantly lower than that in normal subjects and AN patients with DPOAE present, and the nonlinear characteristics decreased on the I/O function curve in patients without DPOAE response, with a more linear tendency in amplitude increasing. 15 , 18 , 19 , 20 In this study, under various stimulation intensities, the CM amplitude of OAE absent group was lower than that of OAE present group, consisted with previous studies. It also found that compared with OAE present group, the CM threshold was higher and duration was shorter in OAE absent group.…”
Section: Discussionsupporting
confidence: 87%
“…Conceivably, CM might be recorded in the absence of OAE if receptor potentials remained intact yet the complex mechanisms underlying active processes and OHCs motility in the cochlea were disrupted. 20 Previous studies showed that the amplitude of CM in AN patients with DPOAE absent was significantly lower than that in normal subjects and AN patients with DPOAE present, and the nonlinear characteristics decreased on the I/O function curve in patients without DPOAE response, with a more linear tendency in amplitude increasing. 15,[18][19][20] In this study, under various stimulation intensities, the CM amplitude of OAE absent group was lower than that of OAE present group, consisted with previous studies.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…However, according to McKnight et al ( 2018) and Lang-Roth et pode estar presente apenas o MC, sendo que as OEA podem estar presentes ou ausentes. Dabbous (2016) reforça esta última teoria, afirmando que a realização das OEA em conjunto com a pesquisa do MC é complementar. Este autor defende ainda que o MC pode estar presente mesmo que as OEA estejam ausentes se apenas os mecanismos e a mobilidade das CCE tiverem sido danificados.…”
Section: Differential Diagnosisunclassified